Do Livelihood Strategies Affect the Livelihood Resilience of Farm Households in Flooded Areas? Evidence From Hubei Province, China - Luo, Xin; Zhang, Chongmei; Song, Jiahao; Qiu, Zishan; Li, Wenzhuo; Wang, Wei (Frontiers in Ecology and Evolution, 2022)
Hubei Province, located in the middle reaches of the Yangtze River, is a complex area of fragile ecological environment and traditional agricultural production in China. With the further intensification of the impact of global warming, flood disasters have brought a more severe threat to the sustainable development of farmers' livelihoods. This paper therefore examines the livelihood resilience of farmers with different livelihood strategies in the region by constructing a livelihood resilience evaluation system based on three target levels: buffering capacity, Adaptation and restoration, and using a contribution model to identify the main contributing factors affecting the livelihood resilience of farmers. The following three conclusions were found: 1. The overall level of livelihood resilience of farmers in flood-affected areas in Hubei Province is not high, and the difference in livelihood resilience indices between farmers with different livelihood strategies is large; 2. Farming-led farmers and part-time balanced farmers can better adapt to external shocks brought about by floods; 3. The main contributing factors affecting the livelihood resilience of various types of farmers have Convergence.